Analisis SWOT Kebijakan Local Currency Settlement Indonesia-China - Aprilia Dwi Rasdiyanti; Suyeno (Faculty of Social and Political Science, 2022)
This research describes the results of the SWOT analysis of the implementation of the Local Currency Settlement (LCS) policy carried out by the countries of Indonesia and China in trade and investment activities. The research uses a literature review as method and using SWOT analysis as an analytical technique with secondary data as a data source. Secondary data were collected from literature reviews of journals, websites, books, and news articles. The results of this discussion include the advantages of implementing LCS such as transaction efficiency, and currency standardization using SNAP, weaknesses in implementing LCS such as currency rate cannot always be the same and will change according to world financial markets, challenges in implementing LCS include data security threats such as Card Skimming, Carding, and Phishing and financial crises such as inflation, as well as opportunities for implementing LCS such as increasing Indonesia's export power to China with easy access to LCS services for large businesses and Indonesian UMKM